Effect of Frailty and Age on Platelet Aggregation and Response to Aspirin in Older Patients with Atrial Fibrillation: A Pilot Study. Issue 1 (June 2016) - Nguyen, Tu; Pepperell, Dominic; Morel-Kopp, Marie-Christine; Cumming, Robert; Ward, Christopher; Hilmer, Sarah
Abstract Introduction Frailty is associated with changes in inflammation, coagulation, and possibly platelet function. Aspirin is still prescribed for stroke prevention in older patients with atrial fibrillation, although not recommended by current guidelines. In frail older people, it is unclear whether platelet aggregability and response to aspirin are altered. This study aims to investigate the effects of frailty and chronological age on platelet aggregability and on responses to aspirin in older patients with atrial fibrillation. Methods Inpatients with atrial fibrillation aged ≥65 years were recruited from a tertiary referral hospital in Sydney, Australia. Frailty was determined using the Reported Edmonton Frail Scale. Platelet aggregation studies were performed using whole blood impedance aggregometry. Results Data from 115 participants were analyzed (mean age 85 ± 6 years, 41% female, 52% frail). Spearman correlation coefficients found no significant associations of platelet aggregation with chronological age or with frailty score. Comparison between frail and non-frail groups showed that there was no impact of frailty status on aggregation assays amongst participants who were not taking any antiplatelet drugs. Amongst participants taking aspirin, the frail had higher adjusted arachidonic acid agonist (ASPI) test measures (AU per platelet) than the non-frail (0.11 ± 0.11 vs. 0.05 ± 0.04;p  = 0.04), suggesting that in frail participants, platelet aggregation is less responsive to aspirin than in non-frail. Conclusions We found no effect of chronological age or frailty status on platelet aggregation amongst older patients with atrial fibrillation in this pilot study. However, frailty could be associated with reduced aspirin responsiveness among older patients with atrial fibrillation.